Magneto‐hydrodynamic mixing: A new technique for preparing carbomer hydrogels. Issue 2 (10th October 2022) - Houlleberghs, Maarten; Verheyden, Loes; Voorspoels, Filip; Chandran, C. Vinod; Duerinckx, Karel; Radhakrishnan, Sambhu; Martens, Johan A.; Breynaert, Eric
Abstract: Magnetohydrodynamic mixing was evaluated as an alternative to conventional high shear mixing (HSM) in the preparation of carbomer hydrogels containing 1.22 wt% Carbopol® 980 NF. Neutralization of the carbomer dispersion (pH = 2.74) with triethanolamine (TEA) enabled to adjust the pH of the mixture and tune the viscosity of the hydrogel. Using HSM, this approach was limited to 0.2 wt% TEA (pH = 3.83) as the gel became too viscous and the recirculation flow dropped from 12 to 0.3 m 3 /h. Magnetohydrodynamic mixing enabled to reach TEA concentrations up to 1.0 wt% (pH = 5.31). Apparent viscosity measurements on samples having 0.2 wt% TEA revealed lower viscosities for carbomer hydrogels prepared with HSM, that is, 6800 mPa s versus 8800 mPa for magneto‐hydrodynamic mixing. Based on 1 H NMR evidence, this decrease in apparent viscosity was attributed to structural damage to the carbomer backbone in combination with mechanochemical degradation of the added TEA.